Protection Algorithm for Fault Identification and Isolation in DC Microgrid - Reddy, N. Nageswara; Velpula, Rajesh; Raja, P.; Moorthi, S. (Distributed Generation & Alternative Energy Journal, 2023)
In renewable energy dominated distributed ring configuration direct current (DC) networks, the protection philosophy is one of the critical challenging task. It is due to the existence of power electronic converters and erratic attributes of distributed energy sources. Consequently, conventional current direction based as well as over current protection strategies is not applicable for DC microgrids. In this paper, protection algorithm for fault recognition and isolation of faulty line is presented based on the polarity of change in inductance immediately after fault inception. The voltage and current sample information is used to determine the parameter by employing the least square estimation (LSE) technique. The efficiency of the proposed method is tested for internal and external faults, the impact of fault resistance and fault location, different system configurations, and load change conditions in MATLAB/Simulink simulation. It is noted that proposed method would categorize internal and external faults perfectly. The operating time of the proposed protection method is comparatively less than the existing methods. It also improves selectivity, security, and reliability under above mentioned abnormal cases.